PERAN BIMBINGAN KONSELING UNTUK SISWA SMP DALAM MENANGANI MASALAH PACARAN - Muhamad Gosani Husni; Radhitya Wisnu; Mahasri Shobabiyah (CV. ADIBA AISHA AMIRA, 2025)
The research that we have made is about the role of a teacher when dealing with dating cases in junior high schools. We explain how the program has been implemented and has had maximum results. This research uses qualitative research methods, with the process of collecting data and information through interviews. Researchers concluded that the role of teachers in dealing with dating problems is very important. One of them is the Class Counseling System program which facilitates all junior high school students to receive counseling guidance services, and a teacher's approach to dealing with students who are dating. Then at the end of the discussion we explain the impact that will occur when students date. This research explains an effective program so that the number of students who have problems dating at Insan Kamil Middle School is a minority. So the role of the counseling teacher in this dating problem greatly influences students' behavior and attitudes.